Demonstration of Binding Induced Structural Plasticity in a SH2 Domain - Visconti, Lorenzo; Toto, Angelo; Jarvis, James A.; Troilo, Francesca; Malagrinò, Francesca; De Simone, Alfonso; Gianni, Stefano (Frontiers in Molecular Biosciences, 2020)
SH2 domains are common protein interaction domains able to recognize short aminoacidic sequences presenting a phosphorylated tyrosine (pY). In spite of their fundamental importance for cell physiology there is a lack of information about the mechanism by which these domains recognize and bind their natural ligands. The N-terminal SH2 (N-SH2) domain of PI3K mediates the interaction with different scaffolding proteins and is known to recognize a specific pY-X-X-M consensus sequence. These interactions are at the cross roads of different molecular pathways and play a key role for cell development and division. By combining mutagenesis, chemical kinetics and NMR, here we provide a complete characterization of the interaction between N-SH2 and a peptide mimicking the scaffolding protein Gab2. Our results highlight that N-SH2 is characterized by a remarkable structural plasticity, with the binding reaction being mediated by a diffused structural region and not solely by the residues located in the binding pocket. Furthermore, the analysis of kinetic data allow us to pinpoint an allosteric network involving residues far from the binding pocket involved in specificity. Results are discussed on the light of previous works on the binding properties of SH2 domains.